1998
DOI: 10.1597/1545-1569_1998_035_0313_stdopa_2.3.co_2
|View full text |Cite
|
Sign up to set email alerts
|

Scar Tissue Distribution on Palates and its Relation to Maxillary Dental Arch Form

Abstract: Objective This study investigated the relationship between maxillary dental arch form and distribution of postsurgical scar tissue on previously denuded bone in isolated cleft palate patients. Method The palatal blood flow of 21 Japanese isolated cleft palate patients (6 males, 15 females) was examined by laser doppler flowmetry to determine the scar tissue areas. All had undergone pushback operations for palatal repair at around 18 months of age. Tissue blood flow was examined at a time ranging from 11 years,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 8 publications
1
20
0
Order By: Relevance
“…The increased amount of collagen type I fibers indicates an increased tensile strength of the submucosa. The increase in tensile strength of the submucosa is one of the factors that impairs maxillary growth after cleft palate surgery (1,3,4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased amount of collagen type I fibers indicates an increased tensile strength of the submucosa. The increase in tensile strength of the submucosa is one of the factors that impairs maxillary growth after cleft palate surgery (1,3,4).…”
Section: Discussionmentioning
confidence: 99%
“…Cleft palate surgery in young patients is considered to be one of the factors causing disturbances in maxillary growth and dento-alveolar development (1). The adverse effects of surgery have been attributed to wound contraction and scarring in the remaining palatal wound (2)(3)(4).…”
mentioning
confidence: 99%
“…1 However, this surgery always causes the denuded bone surface on the palate, thereafter, the scar tissue formation in the open wounds is the major reason accounted for the maxillary growth retardation. 2 Therefore, primary closure of the wounds would be the reasonable intervention for these iatrogenic effects. 3 However, there is still no autologous tissue grafts used for the coverage of the wounds in palatoplasty.…”
Section: Introductionmentioning
confidence: 99%
“…It has been strongly suggested that this scar tissue is a major factor in the impairment of skeletal growth and development of the dentition in both cleft palate patients and animal models. [1][2][3] Myofibroblasts are probably involved in wound contraction. 4,5 These contractile fibroblasts are numerous in many types of contracting wounds.…”
mentioning
confidence: 99%